Scale brightness of common goldfish on diet supplemented with seaweed Sargassum sp. and pumpkin Cucurbita moschata - Irfina Manda Astari; Tri Rima Setyawati; Ari Hepi Yanti (Jurnal Akuakultur Indonesia)
ABSTRACT